Using the Scientific Method to Engage Mathematical Modeling: An Investigation of pi - Lester A. C. Archer; Karen Ng (Journal of Education in Science, Environment and Health)
The purpose of this paper is to explain how to use the scientific method as the framework to introduce mathematical model. Two interdisciplinary activities, targeted for student in grade 6 or grade 7,  are explained to show the application of the scientific method while building a mathematical model to investigate the relationship between the circumferences and the diameter of circular objects. In the first activity, a research question is pursued as it relates to the stated hypothesis. In the second activity, the same research question is retained; however, the use of exploration helps to build the hypothesis. The activities serve as examples to show how middle school math teachers may use scientific inquiry to motive students’ understanding of mathematical models as well as engage in science beyond the science classroom. Students will be able to identify, describe, analyze, interpret, validate, and report relationships between variables.